Risk factors and injury prevention strategies for overuse injuries in adult climbers: a systematic review - Quarmby, A.; Zhang, M.; Geisler, M.; Javorsky, T.; Mugele, H.; Cassel, M.; Lawley, J. (Frontiers in Physiology, 2023)
Introduction Climbing is an increasingly popular activity and imposes specific physiological demands on the human body, which results in unique injury presentations. Of particular concern are overuse injuries (non-traumatic injuries). These injuries tend to present in the upper body and might be preventable with adequate knowledge of risk factors which could inform about injury prevention strategies. Research in this area has recently emerged but has yet to be synthesized comprehensively. Therefore, the aim of this study was to conduct a systematic review of the potential risk factors and injury prevention strategies for overuse injuries in adult climbers.